ANALISIS UJARAN KEBENCIAN PADA KOLOM KOMENTAR AKUN YOUTUBE SCTV TERKAIT KASUS KDRT LESTI KEJORA DAN RIZKY BILLAR - Istiqamah, Istiqamah; Agustin, Tiara Putri; Santi, Chandri Febri; Fanita, Fanita; Khairani, Dwi (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
The purpose of this study was to analyze hate speech in the comments column of the SCTV YouTube account regarding the Leslar Domestic Violence case. The method used in this research is a qualitative method with a descriptive design. The data in this study were collected through observation, listening and reading. The results of the study show that social media is an online-based communication tool that can be used to communicate remotely, not only that we can obtain various kinds of information from social media. This is what makes social media share a positive impact on human social life. Hate speech is interpreted as words, behavior and writing carried out by individuals or groups in the form of provocation, incitement, or insults to other individuals or groups. After conducting an analysis and discussion of hate speech that is rife on social media, it was found that most of the hate speech in the form of words or phrases was deliberately used to express the hatred of device users against an individual, none other than artist Risky Bilar.